Assessment of life-skill for patient adults with diabetes mellitus type II - Khazaal , Qasim Ali; Omer, Ied Ali (University of Thi-Qar Journal, 2019)
Objective: Study aims are to identify the type2 diabetes clients’ life skills, and find out the relationship between variables which are (Age, gender, educational level, duration of DM diagnosis, and monthly income) with type 2 diabetes clients ’life skills. Methodology: Quantitative design descriptive study was carried out through the present investigation from 2 January 2014to 2 July 2014 in order to achieve the objectives of the present study. A non-probability (purposive) sample, (200) cases which consists of clients who were attending An Nasiriyha Diabetic Center. The data were collected by utilization of the study instruments and employment of scheduled personal interview as means data collection. The data collection process was performed from 22/ July / 2014to 2 / November / 2014. A questionnaire was designed constructed by the researcher to measure the variable. Such a construction was employed through the review of literature and related studies. The questionnaire consisted of seven parts which are demographical, and 6 diabetics life skills indicators. The reliability of the questionnaire was determined through a pilot study and the validity through 14 a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient, and contingency coefficient. Results: Highest percent of the study samples (37.5) were (50-59) years old. with the mean age (52±7.1) years, (72%) 0f them are without of type 2 diabetes client’ life skills, were married male, with low educational level. group’s duration of type 2 DM diagnosis was (1-5) years. insufficient monthly income, unemployed, overweight. they had information from their physician, and diagnosed indecently measuring blood glucose level. There were significant association between type 2 diabetes clients’ life skills and (age, educational level, monthly income). And there were no significant association with another variable. Recommendations: The researcher recommended that newly diagnose diabetic patients should be improving life skills by involved in educational program & supply by booklet which include typ2 diabetes clients’ life skills and supported by videotapes to enforce their practices with nurse supervision during visit them to the center .and instructed to periodic blood glucose test, with control their blood sugar and body weight to avoid complications. Nurse in addition to the physician, have an important role to playing the education, counseling and skills building of diabetic patients.